Adapting a robotics program to enhance participation and interest in STEM among children with disabilities: a pilot study. - Lindsay, Sally; Hounsell, Kara Grace (Disability & Rehabilitation: Assistive Technology, 2017)
Purpose:Youth with disabilities are under-represented in science, technology, engineering, and math (STEM) in school and in the workforce. One encouraging approach to engage youth’s interest in STEM is through robotics; however, such programs are mostly for typically developing youth. The purpose of this study was to understand the development and implementation of an adapted robotics program for children and youth with disabilities and their experiences within it. Method:Our mixed methods pilot study (pre- and post-workshop surveys, observations, and interviews) involved 41 participants including: 18 youth (aged 6–13), 12 parents and 11 key informants. The robotics program involved 6, two-hour workshops held at a paediatric hospital. Results:Our findings showed that several adaptations made to the robotics program helped to enhance the participation of children with disabilities. Adaptations addressed the educational/curriculum, cognitive and learning, physical and social needs of the children. In regards to experiences within the adapted hospital program, our findings highlight that children enjoyed the program and learned about computer programming and building robots. Conclusions:Clinicians and educators should consider engaging youth with disabilities in robotics to enhance learning and interest in STEM. Implications for RehabilitationClinicians and educators should consider adapting curriculum content and mode of delivery of LEGO® robotics programs to include youth with disabilities.Appropriate staffing including clinicians and educators who are knowledgeable about youth with disabilities and LEGO® robotics are needed.Clinicians should consider engaging youth with disabilities in LEGO® to enhance learning and interest in STEM.